Evaluating dental students' perspectives on the concurrent teaching of didactic and case‐based courses. Issue 12 (22nd August 2022) - Parikh, Neha; Risinger, Dane; Holland, Julian N; Molony, Donald A; van der Hoeven, Dharini
Abstract: Purpose: To evaluate student perception of integrating biomedical and clinical sciences based on survey of dental students on the concurrent teaching of a didactic systems‐based course and a case‐based course. Methods: First‐year to fourth‐year students (DS1–DS4) students were surveyed for their experiences in concurrent teaching. Student response rate for the survey was 55% (229/420). Pearson's Chi‐squared tests and Kruskal‐Wallis rank sum tests were used to assess statistical significance ( p < 0.05). Results: Of the students surveyed, 83% strongly agreed or agreed that concurrent teaching of the didactic and case‐based courses helped them better understand the biomedical science background and the clinical ramifications ( p < 0.001). On average, 75% percent strongly agreed or agreed that concurrent teaching kept them engaged, motivated, think critically, apply the course content and prepare for clinical practice ( p < 0.001). Of the students surveyed, 69% support expanding concurrent teaching to all four years ( p < 0.001). Mean responses from DS1 and DS4 students differed for questions relating to understanding of biomedical sciences, critical thinking and application to clinic ( p < 0.01). Qualitative data showed that students enjoyed the reinforcement of concepts and application to clinical scenarios. Conclusions: Concurrent teaching of didactic and case‐based learning courses, thus showing clinical relevance of biomedical sciences in the first year of dental curriculum, is perceived by students as an effective method of educating dental students. Such integrative learning process with horizontal and vertical integration and concurrent curriculum is even more relevant with the implementation of the integrated national board dental examination.